96.3k views
3 votes
What is f(-2) for f(x) = x^2+3x=5

2 Answers

3 votes

-2 is x

You put -2 in all the x values, it will turn out like this,

f(-2) = -2^2 + 3(-2) = 5

Let is do to first part of the problem,

f(-2) = -2^2

-2^2 = -4

Okay, now let us combine the equation together and do the second part,

f(-2) = -4 + 3(-2) = 5

Note, that if a number touches a parentheses it means multiplication.

3(-2) = -6

Now let us combine the equation,

f(-2) = -4 + (-6) = 5

Add the following numbers

-4 + (-6) = -10

f(-2) = -10 = 5

Divide

-10 ÷ -10 = 1

-10 ÷ 5 = -2

f(-2) = -2

Note that one will do nothing in the equation so we can leave it out.

You're answer would be -2

Hope this helped! :D

User Bonyem
by
5.5k points
5 votes

f(x) = x^2+3x+5

f(-2) = (-2)^2 +3(-2)+5

f(-2) = 4-6+5

f(-2) = -2+5

f(-2) = 3

User Sasidharan
by
5.4k points